Induction of Hypergammaglobulinemia and Autoantibodies by Salmonella Infection in MyD88-Deficient Mice - Issac, Jincy M.; Mohamed, Yassir A.; Bashir, Ghada Hassan; Al-Sbiei, Ashraf; Conca, Walter; Khan, Taj A.; Iqbal, Asif; Riemekasten, Gabriela; Bieber, Katja; Ludwig, Ralf J.; Cabral-Marques, Otavio; Fernandez-Cabezudo, Maria J.; et al. (Frontiers in Immunology, 2018)
Growing evidence indicates a link between persistent infections and the development of autoimmune diseases. For instance, the inability to control Salmonella infection due to defective toll-like receptor (TLR)/myeloid differentiation primary response 88 (MyD88) signaling has linked the development of persistent infections to a breakdown in B cell tolerance. However, the extent of immune dysregulation in the absence of TLR-MyD88 signaling remains poorly characterized. Here, we show that MyD88−/− mice are unable to eliminate attenuated Salmonella enterica serovar Typhimurium, even when challenged with a low-dose inoculum (200 CFUs/mouse), developing a persistent and progressive infection when compared to wild-type (MyD88+/+) animals. The splenic niche of MyD88−/− mice revealed increased counts of activated, Sca-1-positive, myeloid subpopulations highly expressing BAFF during persistent Salmonella infection. Likewise, the T cell compartment of Salmonella-infected MyD88−/− mice showed increased levels of CD4+ and CD8+ T cells expressing Sca-1 and CD25 and producing elevated amounts of IL-4, IL-10, and IL-21 in response to CD3/CD28 stimulation. This was associated with increased Tfh cell differentiation and the presence of CD4+ T cells co-expressing IFN-γ/IL-4 and IFN-γ/IL-10. Noteworthy, infected MyD88−/− mice had enhanced serum titers of both anti-Salmonella antibodies as well as autoantibodies directed against double-stranded DNA, thyroglobulin, and IgG rheumatoid factor, positive nuclear staining with HEp-2 cells, and immune complex deposition in the kidneys of MyD88−/− mice infected with live but not heat-killed Salmonella. Infection with other microorganisms (Acinetobacter baumanii, Streptococcus agalactiae, or Escherichia coli) was unable to trigger the autoimmune phenomenon. Our findings suggest that dysregulation of the immune response in the absence of MyD88 is pathogen-dependent and highlight potentially important genotype–environmental factor correlations.